Historic salt mines in Wieliczka and Bochnia - Wiewiórka, Janusz; Charkot, Józef; Dudek, Krzysztof; Gonera, Małgorzata (Geotourism/Geoturystyka, 2025)
Historic salt mines in Wieliczka and Bochnia are situated by the old trade road from Kraków to the east, in the region well known from salt-making from brines since the Neolith (ca. 3500 BC). In Bochnia the rock salt was discovered in 1248, whereas in Wieliczka production of the rock salt was confirmed in the town charter in 1290. At the end of the 13th century both mines were united into the Kraków Saltworks. In the 16th century it was the biggest production centre in Poland and one of the biggest in Europe. The rock-salt exploitation ended in Bochnia in 1990 and in Wieliczka in 1996. Both deposits are situated within the Miocene (Badenian – M4) folded strata of the salt-bearing complex, consisting of the Skawina Formation (at the bottom), the Wieliczka Formation (containing the evaporites), and the Chodenice beds (at the top). The Wieliczka deposit consists of the upper boulder deposit and the lower stratiform one. The boulder deposit was formed as a result of submarine flows in southern part of the evaporite basin. Both the boulder and the stratiform deposits were finally shaped by the overthrust movements of the Outer Carpathians. The Bochnia deposit is limited to the northern limb of the Bochnia anticline, at the northern edge of the Outer Carpathians. The Wieliczka Salt Mine is written into the first UNESCO List of the World Cultural and Natural Heritage (1978) and recognised as a National Monument of History (1994). Since 2000 the Bochnia Salt Mine is the National Monument of History as well. In 1997 the Małopolska voivode issued a decree comprising legal protection of 40 documentated sites, important for geology of the Wieliczka deposit, and in 2000 the Natural Reserve “Crystal Caves” in Wieliczka was established. In 2005, twenty seven documentated sites were established and provided with legal protection in the Bochnia Salt Mine.